The Effect of Competence, Training and Work Environment on Employee Performance at PT. Bakrie Sumatera Plantations Tbk, Kisaran: Pengaruh Kompetensi, Training dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Bakrie Sumatera Plantations Tbk, Kisaran - Abdul Rahman; Rosnaida Rosnaida; Henky Japina (Journal of Innovative and Creativity, 2026)
The study purpose was to examine the effect of competence, training, and work environment on employee performance at PT. Bakrie Sumatera Plantations Tbk. This study aims to provide empirical evidence regarding factors that influence employee performance in the plantation sector. Materials and methods. This research employed a quantitative approach with a causal associative design. The population consisted of all employees at PT. Bakrie Sumatera Plantations Tbk, with a total sample of 42 respondents selected using a saturated sampling technique. Data collection was carried out using structured questionnaires, and the data were analyzed using multiple linear regression techniques. Hypothesis testing was conducted through t-test and F-test, supported by classical assumption tests and coefficient of determination analysis. Results. The findings indicate that competence, training, and work environment each have a positive and significant effect on employee performance. Simultaneously, these variables significantly influence employee performance. The coefficient of determination shows that competence, training, and work environment collectively explain a substantial proportion of the variance in employee performance. Conclusions. The study concludes that improving employee competence, implementing effective training programs, and creating a supportive work environment are essential factors in enhancing employee performance at PT. Bakrie Sumatera Plantations Tbk